Redesain Formulir General Consent Rawat Inap Berbasis Elektronik Guna Mengembangkan Medical Record di Rumah Sakit - Rusli, Gilang Sesar Ramadhan; Sufyana, Candra Mecca; Suryani, Ade Irma (Program Studi Teknik Informatika Universitas Pamulang, 2024)
One of the forms that indicates the consent of the patient or the patient's family in relation to the rights and obligations of patients in receiving health care in the hospital is a general consent form. General consent (GC) is a form of general consent that is always submitted to the patients or family before receiving road care and hospital nursing services. Along with rapid scientific and technological advances, the study aims to analyze the design of general consent forms and redesign conventional paper-based forms so that they can be converted into electronic forms. The data collection methods carried out by the authors used qualitative research with a descriptive approach by conducting observations, interviews, and library studies, while the system development methods used in this research used waterfalls. The results of this study are expected to improve and maximize the quality of hospital services.